Expression of mammalian protein kinase C in Schizosaccharomyces pombe: isotype-specific induction of growth arrest, vesicle formation, and endocytosis. - Goode, N T (1994)
Mammalian protein kinase C (PKC) isotypes elicit a number of effects on expression in Schizosaccharomyces pombe. A small decrease in growth rate results from PKC-gamma expression, and treatment of these cells with phorbol esters leads to marked growth inhibition and vesicle formation. PKC-delta and -eta expression causes growth inhibition and vesiculation, and the magnitude of both of these effects is increased by phorbol esters. In contrast, PKC-epsilon expression produces growth inhibition but no vesicle accumulation, and this effect is not responsive to phorbol ester. Finally, PKC-zeta has no observable effect. Thus, isotype-specific biological effects are observed. The accumulation of vesicles correlates with phorbol ester-dependent growth inhibition and occurs only with expression of those isotypes that down-regulate in response to phorbol esters in these cells. Antibodies against mammalian clathrin light chain 1a identified clathrin-coated vesicles and up-regulation of clathrin expression in those cells where vesicles accumulate; the increased vesicular traffic includes an element of endocytosis. Thus expression of specific mammalian PKC isotypes up-regulates endocytosis in S. pombe, providing a likely explanation for PKC-mediated receptor internalization in higher eukaryotes.